Criteria and indicators of the development of work safety and health competence of future specialists in mechanical engineering - Dembitskaya, S. (Problems of Engineer-Pedagogical Education, 2019)
A significant part of the enterprises of the engineering industry of Ukraine is characterized by weak positions in the international market, outdated production technology, inefficient use of existing production facilities, and unstable financial condition. Bringing the engineering industry to a qualitatively new level requires training qualified specialists in machine engineering having not only a sufficient amount of theoretical knowledge and practical skills, but also possessing an ability to independently make production decisions, be mobile, able to adapt to changing working conditions and constantly improve their professional level, at the same time taking into consideration occupational safety and health requirements. To understand the problem situation in the workplace and its effective solution, a mechanical engineering specialist must have corresponding specialized professional knowledge, a high level of fundamental training, and also demonstrate an appropriate level of occupational safety and health competence. Based on the theoretical analysis of scientific publications, the article analyzes the approaches to the definition of the concepts “criterion” and “indicator” in pedagogical research, and also proposes criteria and indicators of the development of occupational safety and health competence of future specialists in mechanical engineering, and identifies levels of its development. Occupational safety and health competence of future specialists in mechanical engineering, which consists of cognitive, motivational, technological and reflexive components, is characterized through theoretical, practical and personal-motivational criteria. The need to take into account the individual characteristics of students in the teaching and learning process gives a reason to identify four levels of the development of occupational safety and health competence such as initial, reproductive, sufficient and creative. Prospects for further development of the scientific research consist in identifying the features of the development of occupational safety and health competence of future specialists in mechanical engineering in the process of industrial engineering internships.